2019
DOI: 10.1002/eap.1861
|View full text |Cite
|
Sign up to set email alerts
|

The past and future roles of competition and habitat in the range‐wide occupancy dynamics of Northern Spotted Owls

Abstract: Slow ecological processes challenge conservation. Short‐term variability can obscure the importance of slower processes that may ultimately determine the state of a system. Furthermore, management actions with slow responses can be hard to justify. One response to slow processes is to explicitly concentrate analysis on state dynamics. Here, we focus on identifying drivers of Northern Spotted Owl (Strix occidentalis caurina) territorial occupancy dynamics across 11 study areas spanning their geographic range an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 28 publications
4
33
1
Order By: Relevance
“…To allow direct comparisons between our study and those conducted in the range of the NSO where habitat conditions (and BO densities) differ (e.g. Yackulic et al, 2019), we calculated landscapescale niche overlap as the proportion of CSO sites at which a BO was also present. Earlier work indicated that CSO site occupancy in our study area was 0.43-0.53 (Wood et al, 2020;Wood, Popescu, et al, 2019), meaning that the BO population could grow to the same size as the CSO population without any overlap in site occupancy.…”
Section: Bioacoustics and Occupancy Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…To allow direct comparisons between our study and those conducted in the range of the NSO where habitat conditions (and BO densities) differ (e.g. Yackulic et al, 2019), we calculated landscapescale niche overlap as the proportion of CSO sites at which a BO was also present. Earlier work indicated that CSO site occupancy in our study area was 0.43-0.53 (Wood et al, 2020;Wood, Popescu, et al, 2019), meaning that the BO population could grow to the same size as the CSO population without any overlap in site occupancy.…”
Section: Bioacoustics and Occupancy Modellingmentioning
confidence: 99%
“…Over the last century, barred owls (BOs; Strix varia) have expanded from eastern North America into much of western North America, including the range of the northern spotted owl (NSO; S. occidentalis caurina), a process that was likely facilitated by anthropogenic landscape change (Livezey, 2009). The two species can hybridize, and the competitively superior BO poses an existential threat to the NSO (Dugger et al, 2015;Hanna et al, 2018;Wiens et al, 2014;Yackulic et al, 2019). Barred owl density in the Sierra Nevada, the core range of the CSO (CSO; S. o. occidentalis), is low but increasing , indicating that the invasion of that region is still in its early stages.…”
Section: Introductionmentioning
confidence: 99%
“…Those mismatches are further illustrated by the manner in which the differential forest management histories on private lands (intensive timber extraction), national forests (large tree logging and fire suppression), and national parks (limited logging history and increased use of fire) in the Sierra Nevada have mediated spotted owl territory survival via its influence on their small mammal prey (Hobart et al 2019b). Importantly, the Sierra Nevada population of the California spotted owl is threatened by other processes, notably (i) a rapidly growing barred owl population (Wood et al in review) that could cause further spotted owl population declines through conspecific aggression and competition (Yackulic et al 2019), and (ii) the possibility of widespread and persistent environmental toxicity via anticoagulant rodenticides that can cause direct…”
Section: Multidimensional Trade-offs and Spatiotemporal Mismatchesmentioning
confidence: 99%
“…Maintain forested ecosystems owl mortality through food chain contamination (Franklin et al 2018, Gabriel et al 2018. These threats can interact, but, importantly, the return on management investments may be realized on very different time scales (Yackulic et al 2019), incentivizing a cautious and comprehensive approach to spotted owl conservation. An important consequence of the complexity of the social-ecological system that is the modern Sierra Nevada is the propensity for the ramifications of forest management decisions to ripple in space and time.…”
Section: Ecosystem Type Conversionmentioning
confidence: 99%
“…Over the past century, Barred Owls (Strix varia) have expanded their geographic range west from eastern North America, and their newly expanded range now completely overlaps that of the federally threatened Northern Spotted Owl (S. occidentalis caurina). Evidence indicates that competition with invading Barred Owls has contributed significantly to declines in populations of Spotted Owls (Wiens and others, 2014;Dugger and others, 2016;Yackulic and others, 2019). A pilot study in coastal California demonstrated that removal of Barred Owls in combination with conservation of suitable forest conditions can slow or even reverse the rate of population decline in Spotted Owls others, 2014, 2016).…”
Section: Background and Study Objectivesmentioning
confidence: 99%